Voices from the stories untold: Lesbian, gay, bisexual, trans, and queer college students' experiences with campus climate. Issue 4 (2nd October 2017) - Evans, Rosalind; Nagoshi, Julie L.; Nagoshi, Craig; Wheeler, Jeffrey; Henderson, Jeremiah
ABSTRACT: Twelve self-identified college students within the lesbian, gay, bisexual, transgender, and queer (LGBTQ) spectrum were interviewed on campus climate perceptions and their experiences of discrimination and isolation at their university. Thematic analysis was conducted to identify themes from the data. This process resulted in the emergence of three themes, identified as discrimination, isolation, and avoidance. The most salient experiences of discrimination and isolation reported by participants came from within LGBTQ organizations or from lesbian or gay male individuals that participants sought out for social support. LGBTQ intra-community discrimination was considered to be particularly damaging to participants' sense of belonging and involvement within the LGBTQ community. Discrimination and isolation from straight-identified organizations or individuals was reported mostly in the context of fraternities/sororities and religious organizations. Furthermore, actions by members of these latter groups caused participants to avoid these groups out of expectations of negative interactions. These results inform empirical research to bring awareness to acts of discrimination that continue to take place within the university toward LGBTQ students. Specific implications for social work practice with LGBTQ college students and future research on diverse LGBTQ populations and resources are discussed.